2013
DOI: 10.1021/pr400274w
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Analysis of Bronchoalveolar Lavage (BAL) Fluid Identifies Tumor-Associated Glycoproteins from Lung Adenocarcinoma

Abstract: Cytological examination of cells from bronchoalveolar lavage (BAL) is commonly used for the diagnosis of lung cancer. Proteins released from lung cancer cells into BAL may serve as biomarkers for cancer detection. In this study, N-glycoproteins in 8 cases of BAL fluid, as well as 8 lung adenocarcinoma tissues and 8 tumor-matched normal lung tissues, were analyzed using the solid-phase extraction of N-glycoprotein (SPEG), iTRAQ labeling and liquid chromatography tandem mass spectrometry (LC-MS/MS). Of 80 glycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…All these proteins have been reported to show potential anticancer effects. Whereas, other proteins, such as LPCAT2 that is highly expressed in inflammatory cells [ 22 ], BPIFA3 that is highly expressed in lung cancer [ 23 ], PPIA that activates NFkB pathway [ 24 ], and FABP4 that has pro-angiogenic role [ 25 ], were downregulated in SBP1 overexpression xenograft tumors. In contrast, seven glucose metabolism-related proteins were significantly downregulated in SBP1 overexpression xenograft tumors, including GAA, GAPDH, ALDH2, Thioredoxin, ENO3, UGDH and Lumican ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All these proteins have been reported to show potential anticancer effects. Whereas, other proteins, such as LPCAT2 that is highly expressed in inflammatory cells [ 22 ], BPIFA3 that is highly expressed in lung cancer [ 23 ], PPIA that activates NFkB pathway [ 24 ], and FABP4 that has pro-angiogenic role [ 25 ], were downregulated in SBP1 overexpression xenograft tumors. In contrast, seven glucose metabolism-related proteins were significantly downregulated in SBP1 overexpression xenograft tumors, including GAA, GAPDH, ALDH2, Thioredoxin, ENO3, UGDH and Lumican ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple biomarkers detectable in bronchial fluids from lung cancer patients have been proposed [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Recently, we have shown that lung cancer cells efficiently activate the classical pathway of complement.…”
Section: Introductionmentioning
confidence: 99%
“…To study glycoprotein expression, researchers have developed a strategy called solid-phase extraction of N-linked glycopeptides (SPEG) to isolate N-linked glycopeptides from biological samples, wherein digested peptides are conjugated to a hydrazide resin and specifically released using peptide-N-glycosidase F 33 . This strategy has been used to identify glycoprotein expression patterns and alterations in a variety of cancer types including ovarian 34 , prostate cancer 35 , breast cancer 36 , and lung cancer 12 , 37 . A limitation of the SPEG technique we used in this study is that it is protein-centric, and information regarding the structure and composition of attached glycan is lost.…”
Section: Discussionmentioning
confidence: 99%